The Nature of Educators from the Perspective of Islamic Educational Philosophy - Maspuroh; Silvi Sofiatul Alawiyah; Siti Rubaiah; Muhammad Imam Akhfas; Siti Alsa’adah (Penerbit Hellow Pustaka, 2024)
Educators are people who are entrusted and have responsibility in the afterlife in educating, guiding, directing and delivering students to happiness in the afterlife. An educator not only provides knowledge to his students but also provides knowledge on how to educate his students to become good people. Therefore, to become a quality educator, one must have the same criteria as Muslim educators. The aim of this journal is to understand the essence of the role of educators from the perspective of the philosophy of Islamic religious education. This journal explores the meaning of educator in the context of Islamic education, using several terms in Arabic such as mu'allim, mu'addib, and murabbi.